Risk Factors of Cardiovascular Disease among Rural Population in Southern India - Mendagudli, Roopa R; Manjula R; Nigudgi, Shantkumar R (National Journal of Community Medicine, 2018)
Background and Objectives: The study was conducted to study the magnitude of risk factors of cardiovascular disease (CVD) among rural population in Southern India. Methodology: A community based cross sectional study was conducted in Shirur, Bagalkot. The study was conducted among a sample of 1226 respondents aged 20 years and above by systematic random sampling method. Information on socio-demographic and risk factors of cardiovascular disease collected by interview method using a pre-designed, semi structured proforma. Results: Of the total 1226 respondents, 539 were males & 687 females with the mean age 45.06 (±16.08) years and 44.27(±16.48) years respectively. There was significant difference (p<0.05) noticed in family history of hypertension, nature of work, dietary pattern. Men had significantly higher mean systolic blood pressure (124.8±16.1mmHg), serum fasting plasma glucose (101.9±30.9 mg/dl), serum post prandial plasma glucose (101.9±30.9 mg/dl), WHR (0.87± 0.08). Conclusion: The present study revealed that the higher rates of risk factors like family history of hypertension, sedentary nature of work, mixed diet pattern, obesity, smoking and alcohol consumption. The higher levels of diastolic blood pressure and significantly different levels of distribution fasting blood sugar and total cholesterol levels among males and females is the matter of concern.